Diminishing Speckle Noise during Nonlinear Phase-Only Beam Shaping - Ackermann, Lisa; Roider, Clemens; Cvecek, Kristian; Barré, Nicolas; Schmidt, Michael (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
The liquid crystal spatial light modulator (LC-SLM) is a powerful device to dynamically shape arbitrary intensity distributions and finds application in research and industry. While wave front shaping is highly efficient and thus favorable, the shaped intensity profile suffers from speckle noise and, moreover, LC-SLMs are technically limited to the visible, near-infrared and mid-infrared spectral ranges. We make use of nonlinear optics to enlarge the spectral range by shaping the light field at the fundamental but achieving the desired outcome at the second harmonic [1]. Moreover, we diminish speckle noise by temporal averaging to achieve results of high uniformity and quality. To this end, usually several different patterns are displayed sequentially on the SLM what results in poor efficiency due to the low frame rate. We overcome this problem by using a single phase mask while the beam is scanned over the SLM with a galvanometer scanner and subsequently de-scanned [2].
CRIS-Team Scopus Importer:2024-12-16

Diminishing Speckle Noise During Nonlinear Phase-only Beam Shaping - Ackermann, Lisa; Roider, Clemens; Cvecek, Kristian; Barré, Nicolas; Schmidt, Michael (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
The liquid crystal spatial light modulator (LC-SLM) is a powerful device to dynamically shape arbitrary intensity distributions and finds application in research and industry. While wave front shaping is highly efficient and thus favorable, the shaped intensity profile suffers from speckle noise and, moreover, LC-SLMs are technically limited to the visible, near-infrared and mid-infrared spectral ranges. We make use of nonlinear optics to enlarge the spectral range by shaping the light field at the fundamental but achieving the desired outcome at the second harmonic [1]. Moreover, we diminish speckle noise by temporal averaging to achieve results of high uniformity and quality. To this end, usually several different patterns are displayed sequentially on the SLM what results in poor efficiency due to the low frame rate. We overcome this problem by using a single phase mask while the beam is scanned over the SLM with a galvanometer scanner and subsequently de-scanned [2].
CRIS-Team Scopus Importer:2024-12-16

Direct laser-written aperiodic photonic volume elements for complex light shaping with high efficiency: inverse design and fabrication - Barré, Nicolas; Shivaraman, Ravi; Moser, Simon; Salter, Patrick S.; Schmidt, Michael; Booth, Martin J.; Jesacher, Alexander (Advanced Photonics Nexus, 2023)
Light plays a central role in many applications. The key to unlocking its versatility lies in shaping it into the most appropriate form for the task at hand. Specifically tailored refractive index modifications, directly manufactured inside glass using a short pulsed laser, enable an almost arbitrary control of the light flow. However, the stringent requirements for quantitative knowledge of these modifications, as well as for fabrication precision, have so far prevented the fabrication of light-efficient aperiodic photonic volume elements (APVEs). Here, we present a powerful approach to the design and manufacturing of light-efficient APVEs. We optimize application-specific three-dimensional arrangements of hundreds of thousands of microscopic voxels and manufacture them using femtosecond direct laser writing inside millimeter-sized glass volumes. We experimentally achieve unprecedented diffraction efficiencies up to 80%, which is enabled by precise voxel characterization and adaptive optics during fabrication. We demonstrate APVEs with various functionalities, including a spatial mode converter and combined intensity shaping and wavelength multiplexing. Our elements can be freely designed and are efficient, compact, and robust. Our approach is not limited to borosilicate glass but is potentially extendable to other substrates, including birefringent and nonlinear materials, giving a preview of even broader functionalities, including polarization modulation and dynamic element
Keywords: integrated photonics; holography; mode conversion; inverse design

Polarization-Controlled Nonlinear Computer-Generated Holography - Ackermann, Lisa; Roider, Clemens; Cvecek, Kristian; Barré, Nicolas; Aigner, Christian; Schmidt, Michael (Scientific Reports, 2023)
Dynamic phase-only beam shaping with a liquid crystal spatial light modulator is a powerful technique for tailoring the beam's intensity profile or wave front. While shaping and controlling the light field is a highly researched topic, dynamic nonlinear beam shaping has hardly been explored so far. One potential reason is that generating the second harmonic is a degenerate process as it mixes two fields at the same frequency. To overcome this problem, we propose the use of type II phase matching as a control mechanism to distinguish the two involved fields. We experimentally demonstrate that arbitrary intensity distributions can be shaped in the frequency-converted field at the same quality as for linear beam shaping and with conversion efficiencies similar to the case without beam shaping. We envision this technique as a milestone towards beam shaping beyond the physical limits of liquid crystal displays, i.e. facilitating dynamic phase-only beam shaping in the ultraviolet spectral range.
Keywords: phase-only beam shaping; nonlinear holography; second harmonic generation; nonlinear optics